Sistem Informasi Data Pinjaman Nasabah Berbasis Web di Bank Syariah Indonesia (BSI) - Ira Zulfa; Richasanty Septima; Pitri Indriani (STMIK Budi Darma, 2023)
Bank Syariah Indonesia is a bank that carries out business activities based on sharia principles or the principles of Islamic law (UU No. 21 of 2008 concerning Islamic Banking). The main function of Indonesian banking is to collect and distribute public funds and aims to support the implementation of national development in the context of increasing the distribution of development and its results, economic growth and national stability, towards increasing the standard of living of the people at large. Generally there are two forms of business from the Islamic bank itself. The first is an Islamic commercial bank and the second is an Islamic people's financing bank (BPRS). The two types of Islamic bank businesses have the same basic function in collecting and distributing public funds (lending funds to customers). Every day many customers come to process loans. However, due to the absence of a helpful system, the customer loan process and customer data recording are still carried out manually, namely recorded in a ledger, causing many problems, such as untidy monthly reports, calculation errors, data that is not updated and many more problems. found in connection with lending and payment activities. The